The neutron capture process in the He shell in core-collapse supernovae: Presolar silicon carbide grains as a diagnostic tool for nuclear astrophysics. (15th January 2018) - Pignatari, Marco; Hoppe, Peter; Trappitsch, Reto; Fryer, Chris; Timmes, F.X.; Herwig, Falk; Hirschi, Raphael
Abstract: Carbon-rich presolar grains are found in primitive meteorites, with isotopic measurements to date suggesting a core-collapse supernovae origin site for some of them. This holds for about 1–2% of presolar silicon carbide (SiC) grains, so-called Type X and C grains, and about 30% of presolar graphite grains. Presolar SiC grains of Type X show anomalous isotopic signatures for several elements heavier than iron compared to the solar abundances: most notably for strontium, zirconium, molybdenum, ruthenium and barium. We study the nucleosynthesis of zirconium and molybdenum isotopes in the He-shell of three core-collapse supernovae models of 15, 20 and 25 M☉ with solar metallicity, and compare the results to measurements of presolar grains. We find the stellar models show a large scatter of isotopic abundances for zirconium and molybdenum, but the mass averaged abundances are qualitatively similar to the measurements. We find all models show an excess of 96 Zr relative to the measurements, but the model abundances are affected by the fractionation between Sr and Zr since a large contribution to 90 Zr is due to the radiogenic decay of 90 Sr. Some supernova models show excesses of 95, 97 Mo and depletion of 96 Mo relative to solar. The mass averaged distribution from these models shows an excess of 100 Mo, but this may be alleviated by very recent neutron-capture cross section measurements. We encourage future explorations to assess the impact of the uncertainties in key neutron-capture reaction rates that lie along the n -process path.